Experimental evidence of runaway electron tail generation via localized helical structure in pellet-triggered tokamak disruptions. (13th September 2021) - Du, X.D.; Eidietis, N.W.; Hollmann, E.M.; Finkenthal, D.; Stagner, L.; Paz-Soldan, C.; Strait, E.J.; Barr, J.L.; Lvovskiy, A.
Abstract: A novel detector, using stacked BGO crystals, is developed for runaway electron (REs) studies in the DIII-D tokamak. It is able to resolve fast dynamics of high-energy tail formation of REs with an ultra-high time resolution of ∼1  μ s. As a cost, the detector estimates the 'effective' energy of a given shape of γ-ray spectra and sacrifices the energy resolution. In aid of the new measurement capability, a rapid, inhomogeneous growth of RE tail is observed in detail during a major disruption triggered by an argon pellet. It is found that both the population and energy of a well-confined RE tail significantly oscillate at the early period of the growth. The oscillation phase is locked to a slow rotating magnetohydrodynamic instability, which is briefly destabilized for only ∼1 ms at the early period of the current quench. The oscillation ceases promptly, when the mode disappears. The data suggests that the high-energy RE tail is well-confined and accelerated via a localized helical structure in the plasma core.